PENGARUH DUKUNGAN KELUARGA TERHADAP KUALITAS HIDUP PASIEN DIABETES MELITUS DI RUMAH SAKIT UMUM ROYAL PRIMA - Lubis, Lisnawati; Meliana, Sari; Nurhayati, Evalatifah; Debora, Trionyta; Rahmi, Intan Mutia; Siregar, Patimah Sari (Universitas Murni Teguh, 2024)
Diabetes mellitus or diabetes, is when the body cannot use the insulin produced by the pancreas efficiently or cannot make enough insulin hormone, an increase in blood glucose levels occurs. High blood glucose is caused by a lack of insulin or a failure of cells to respond to it. The role and support of the family plays an important role in the quality of life of DM patients. This study aims to determine the effect of family support on the quality of life of Diabetes Mellitus patients at the Royal Prima General Hospital. This research design uses a